Effectiveness of Petai (Parkia speciosa) Ethanol Extract in Controlling Foam Cell Numbers in Atherosclerosis-Induced Male Wistar Rats - Ikhwan Handirosiyanto; Indra setiawan; Seftiana Khaerun Nisa; Dian Yuliartha Lestari (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Atherosclerosis is a chronic inflammatory disease that causes the narrowing of the arterial lumen, and it is considered the primary cause of cardiovascular diseases such as myocardial infarction (MI), heart failure, and stroke. Cardiovascular disease is the leading of death globally. Atherosclerosis has a complex pathophysiology, such as endothelial dysfunction, thickening of the tunica intima, and the formation of atheromatous plaques. After that process, foam cells will form, which is the key to the development of atherosclerosis. Petai ethanol extract contains antioxidants, which are flavonoids, saponins, and tannins, that can reduce the number of Low-Density lipoproteins (LDL). The purpose of this study was to evaluate the effect of petai ethanol extract on the number of atherosclerotic foam cells in male white rats (Rattus norvegicus strain wistar) induced by lard. The method of this study was a genuinely experimental and post-test-only control group design with 25 rats divided into five control groups, which are one negative control group, one positive control group, and three treatment groups with extract doses of 100mg/kgBW, 200mg/kgBW and 400mg/kgBW. Observation of foam cells was carried out using a microscope with 400x magnification. Data were analyzed using Oneway ANOVA and Post Hoc Tamhane's test. The results of the study using the Oneway ANOVA test showed that there were significant differences between groups (p: 0.000). Post Hoc Tamhane's test between the positive control group and treatment groups 1, 2, and 3 can be seen that there is a significant difference between the formation of foam cells due to the administration of petai ethanol extract compared to positive control (p <0.05). This study concludes that Petai ethanol extract was effective in reducing the number of atherosclerotic foam cells formed.